EFFORTS TO IMPROVE TEACHERS IMPLEMENTING CAPABILITIES THROUGH CHARACTER EDUCATION TECHNICAL SUPERVISION GROUP AT STATE ELEMENTARY SCHOOL 17 PANYAKALAN DISTRICT OF SOLOK DISTRICT KUBUNG - Mulyadi Mulyadi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
Character education is one very important aspect is developed in school. The development of character education has become a national agenda and should be integrated into the curriculum. Based on the beginning observations of the teachers of State Elementary School 17 Panyakalan District of Kubung indicated the ability of teachers to implement character education is still low. This phenomenon is closely linked to the suspected teachers who still lack understanding about concepts of character education, how to integrate character values ​​into the curriculum has not been mastered, as well as the assessment and follow-up has not been understood. This research is a school action aimed to reveal one of the techniques that can be used to improve the ability of teachers to apply character education. The technique that used is the technique of group supervision. namely: providing guidance to the teacher in groups. Researchers conducted a guidance to teachers in small groups and teachers collaborate and cooperate. Hypothesis actions proposed in this study is to use the technique of group supervision can improve the ability of teachers to apply character education at State Elementary School 17 Panyakalan District of Kubung. School action research subjects are all teachers civil servants and non-civil servants State Elementary School 17 Panyakalan District of Kubung are a total of 11 people. The procedure of research consisted of four stages: planning, action, observation, and reflection. Cycle performed in this study as much as two cycles. Each cycle carried out 2 times a supervision activities. Data were obtained from observations and the work in the form of a syllabus and lesson plans and then analyzed. School action research analysis results indicate that there is an increase in the ability of teachers to implement character education In addition, the teachers showed a positive attitude and high motivation to implement character education in the schools. The result of this research showed that ability of teachers are increase in applying the character education at State Elementary School 17 Panyakalan District of lemur can be done by using the group supervision. The conclusion of this study showed an increased ability of teachers to implement character education at State Elementary School 17 Panyakalan District of lemur through the technique of group supervision. This is evidenced by the increased activity of students while studying in cycle 1 and cycle 2.